2006
DOI: 10.1088/0268-1242/21/7/024
|View full text |Cite
|
Sign up to set email alerts
|

Inductively coupled plasma reactive ion etching of ZnO using C2F6and NF3-based gas mixtures

Abstract: Inductively coupled plasma reactive ion etching (ICP RIE) of ZnO film using C 2 F 6 and NF 3 -based gas mixtures was investigated as a function of ICP power, bias power, pressure, and plasma chemistry. An etch rate of about 410 nm min −1 in the case of C 2 F 6 plasma and about 380 nm min −1 in the case of NF 3 plasma was obtained at the optimum condition, with vertical sidewalls and smooth surfaces, which is about 30% higher than the etch rates obtained in the previous reports on ICP RIE of ZnO using CH 4 or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…and by high precision procedures. 43,44 Moreover, studying the systematic variations in the critical dimensions, we have scaled up/down the in-plane dimensions of the design for ±5% and show that the central peak frequencies change inversely by the scaling factor and the peak intensities show an overall drop between 1 and 3 dB, which is acceptable.…”
Section: Journal Of Applied Physicsmentioning
confidence: 97%
“…and by high precision procedures. 43,44 Moreover, studying the systematic variations in the critical dimensions, we have scaled up/down the in-plane dimensions of the design for ±5% and show that the central peak frequencies change inversely by the scaling factor and the peak intensities show an overall drop between 1 and 3 dB, which is acceptable.…”
Section: Journal Of Applied Physicsmentioning
confidence: 97%
“…The thin film was then selectively etched using ICP RIE (custom Plassys system) with C 2 F 6 [6] with the metallic mesas acting as a mask. Parameters were adjusted so as to remove the metal and etch 65-70 nm down into the ZnO film.…”
Section: Nanopatterningmentioning
confidence: 99%
“…Lee, et al, 13 has recently reported ICP etching of ZnO in C 2 F 6 and NF 3 plasmas. One might expect the etch rate in fluorinated gases to be lower than in chlorinated gases due to the differences in the vapor pressures of possible etch products such as zinc fluoride and zinc chloride (7.5 mTorr or 1 Pa at a temperature of 731°C and 305°C respectively), 14 however, etch rates near 400 nm/min, with smooth surfaces and reasonably vertical sidewalls were obtained for both gases.…”
Section: Highlights Of Recently Published Workmentioning
confidence: 99%
“…al., has reported even higher etch rates (~400 nm/min) with smooth and anisotropic profiles in C 2 F 6 and NF 3 chemistries. 13 …”
Section: Introductionmentioning
confidence: 99%